Electrolyzed hypochlorous acid water exhibits potent disinfectant activity against various viruses through irreversible protein aggregation - Dianty, Rahmi; Hirano, Junki; Anzai, Itsuki; Kanai, Yuta; Hayashi, Tsuyoshi; Morimoto, Masae; Kataoka-Nakamura, Chikako; Kobayashi, Sakura; Uemura, Kentaro; Ono, Chikako; Watanabe, Tokiko; Kobayashi, Takeshi; et al. (Frontiers in Microbiology, 2023)
It is essential to employ efficient measures to prevent the transmission of pathogenic agents during a pandemic. One such method involves using hypochlorous acid (HClO) solution. The oxidative properties of HClO water (HAW) can contribute to its ability to eliminate viral particles. Here, we examined a highly purified slightly acidic hypochlorous acid water (Hp-SA-HAW) obtained from the reverse osmosis membrane treatment of an electrolytically-generated SA-HAW for its anti-viral activity and mode of action on viral proteins. Hp-SA-HAW exhibited broad-spectrum antiviral effects against various viruses, including adenovirus, hepatitis B virus, Japanese encephalitis virus (JEV), and rotavirus. Additionally, Hp-SA-HAW treatment dose-dependently resulted in irreversibly aggregated multimers of the JEV envelope and capsid proteins. However, Hp-SA-HAW treatment had no discernible effect on viral RNA, indicating that Hp-SA-HAW acts against amino acids rather than nucleic acids. Furthermore, Hp-SA-HAW substantially reduced the infectivity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including the ancestral variant and other multiple variants. Hp-SA-HAW treatment induced the aggregation of the SARS-CoV-2 spike and nuclear proteins and disrupted the binding of the purified spike protein of SARS-CoV-2 to human ACE2. This study demonstrates that the broad-spectrum virucidal activity of highly purified HClO is attributed to viral protein aggregation of virion via protein oxidation.